Improving the conceptual understanding of the Darajat Geothermal Field. (January 2020) - Intani, Rindu G.; Golla, Glenn U.; Syaffitri, Yunia; Paramitasari, Hanna M.; Nordquist, Gregg A.; Nelson, Chris; Ginanjar,; Giri, Gede K.D.S.; Sugandhi, Arias
Abstract: The Darajat Geothermal Field is the largest vapor-dominated geothermal field in Indonesia with an installed power generation capacity of 271 MWe. For the past 23 years, it has averaged about 90% net capacity factor since commercial operations started in 1994. From the initial 55 MWe, new increments of generation were added in 2000 (95 MWe) and in 2007 (110 MWe; later increased to 121 MWe in 2009). The drilling of wells to support these new increments of generation and continuous resource monitoring has provided key data for integration into the conceptual model and resource simulation modelling. Recent reservoir characterization studies enabled the delineation of surface structures that impact the geothermal system, correlation of surface and subsurface rocks, determination of the orientation of fractures that correlate with feed zones encountered by wells, and better imaging of the reservoir through use of advanced geophysical interpretation methods. The above analyses have helped better define the conceptual model of the Darajat Field and provided information in targeting future make-up wells. Star Energy Geothermal Darajat II (SEGD) takes a proactive approach to manage anticipated and emerging resource performance issues. A good example of this approach is provided by adjustments to the injection of steam condensate from the power plants. Injection initially utilized low productivity wells in the central portion of the field. Field monitoring through geochemical, downhole, and wellhead pressure-temperature ("PT ") measurements indicated that this injection strategy had the potential to adversely affect production from nearby wells by suppressing aquifer boiling and lowering reservoir pressure. Consequently, in 2012, condensate injection was shifted to a new location near the Northeast margin of the field to utilize a well with deep entries. Based on experience and supported with case histories from other vapor-dominated fields, primarily The Geysers, deep injection beneath the feed zones of the production wells is effective at minimizing the impacts of injection breakthrough. Following the change in injection strategy, the central portion of the field has experienced renewed boiling, while only one production well is exhibiting early symptoms of chemical breakthrough from injection in the Northeast. Going forward, expected reservoir management challenges include requirements to add new well pads and target production wells into undrilled areas, localized increased influx of external fluids as the reservoir pressure drops, and reservoir dry-out leading to high superheat levels and reduced well productivity. By continuing to leverage lessons learned to further improve reservoir management processes along with the proactive response to field management issues, SEGD anticipates that Darajat can maintain its production at current levels for the forseeable future.